1987
DOI: 10.1136/emj.4.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Femoral nerve block in the initial management of femoral shaft fractures.

Abstract: The aim of this study was to demonstrate that the under-used technique of femoral nerve block (F.N.B.) (Berry, 1977) has excellent analgesic action for femoral shaft fractures when performed by junior staff. It had no recorded side effects and was used in all age groups for fractures at all levels along the femoral shaft. Twenty-seven consecutive patients were studied as they presented in an accident room, all received a femoral nerve block (10 ml 1% Lignocaine with 1:200000 adrenaline) from unsupervised junio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…Excess sedation can impair patients' ability to communicate regarding symptoms of intraneural or intravascular injections, which is an important safety feature [37,38]. Supplementary regional blocks may also aid patient positioning and prolong postoperative analgesia [39,40]. Surgical positioning should be delayed until surgical anesthesia is established.…”
Section: Regional Anesthetic Technique Performancementioning
confidence: 99%
“…Excess sedation can impair patients' ability to communicate regarding symptoms of intraneural or intravascular injections, which is an important safety feature [37,38]. Supplementary regional blocks may also aid patient positioning and prolong postoperative analgesia [39,40]. Surgical positioning should be delayed until surgical anesthesia is established.…”
Section: Regional Anesthetic Technique Performancementioning
confidence: 99%
“…[26] minutes with lidocaine alone. [25][26][27]61] Bupivacaine 0.5% has been reported to be safe and effective in doses of 1-2 mg/kg (0.2-0.4 Technique mL/kg) for femoral nerve block in children with fractures in the Femoral nerve block is achieved by injecting local anesthetic ED. Grossbard and Love [25] used bupivacaine 1 mg/kg, Denton adjacent to the femoral nerve at the level of its division into and Manning [26] used bupivacaine 1.5 mg/kg, Ronchi et al [27] used terminal branches within the femoral triangle just below the inguibupivacaine 2 mg/kg, and Khoo and Brown [62] used bupivacaine nal ligament (see figure 1).…”
Section: Femoral Nerve Blockmentioning
confidence: 99%
“…The nerve lies just deep to the facia iliaca, which forms the dren receiving the higher dose. If bupivacaine is unavailable, posterior aspect of the femoral sheath containing the femoral vein Grossbard and Love, [25] and McGlone et al [61] reported 1% lidoand artery. To reach the femoral nerve, the skin is prepared using a caine with epinephrine at 1 mg/kg (0.1 mL/kg) to be safe and sterile technique then, through a 30-gauge needle, 0.1-0.2mL of effective, whereas Dalens [30] recommends the routine use of lidobuffered lidocaine is injected subcutaneously 0.5-1cm lateral to caine 5 mg/kg.…”
Section: Femoral Nerve Blockmentioning
confidence: 99%
“…This ultrasound-guided block is a safe and simple technique for anesthesia in femur fractures and soft tissue injuries of the anterior thigh. [124][125][126][127][128][129][130][131][132][133] The 3-in-1 FNB is a variation of the fascia iliaca and FNB, targeting the lateral cutaneous nerve of the thigh and obturator nerve. It requires more local anesthetic and direct pressure 2-4 cm distal to the injection site to allow anesthesia of both branches of the femoral nerve.…”
Section: Peripheral Nerve Blockadementioning
confidence: 99%